2017
DOI: 10.1590/1981-6723.14216
|View full text |Cite
|
Sign up to set email alerts
|

Compostos bioativos e características físico-químicas de polpa de araticum in natura e pasteurizada

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado. Compostos bioativos e características físico-químicas de polpa de araticumin natura e pasteurizada Bioactive compounds and physicochemical characteristics of in natura and pasteurized araticum pulp ResumoO objetivo deste trabalho foi avaliar o potencial antioxidante, o teor de com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
1
7
1
3
Order By: Relevance
“…Braga (Figure 2A), which showed stability tendency until the 210th day of storage, and subsequently the values were increased, which occurred due to the sharp fall in acidity. Lower SS/TA values were found by Morais et al (2017) when they analyzed the fresh pulp (32,36) and the pasteurized pulp (31,49).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Braga (Figure 2A), which showed stability tendency until the 210th day of storage, and subsequently the values were increased, which occurred due to the sharp fall in acidity. Lower SS/TA values were found by Morais et al (2017) when they analyzed the fresh pulp (32,36) and the pasteurized pulp (31,49).…”
Section: Resultsmentioning
confidence: 92%
“…On the other hand, Silva et al (2015) observed that there was no change in titratable acidity levels during storage for 180 days of araticum's pulp submitted to bleaching or pasteurization process and then frozen at -5ºC or -18ºC. Morais et al (2017) evaluated the in natura and pasteurized araticum's pulp and found titratable acidity levels of 0,30g of malic acid 100 g-1 of pulp for both the in natura and the pasteurized pulp, which was lower than that was found in this work during storage.…”
Section: Resultsmentioning
confidence: 99%
“…The fruits of the Cerrado have been highlighted due to the flavor and aroma and represent a source of good fiber and antioxidants (Morais et al, 2017) and their use in the development of new products represents an important alternative. Furthermore, it contributes to the large consumption of fruits and milk, provides an entirely new experience in terms of flavor, and promotes sustainable extractivism, thereby strengthening existing markets and intensifying the conquest of new markets.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we highlight the major components with bioactive properties that have specific metabolic or physiological actions. These include the presence of important micronutrients such as vitamins C and A, as well as antioxidant activity (Morais et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, these fruits are quite perishable, and the bioactive compounds are prone to easy degradation. To avoid such losses and add value to these products, postharvest conservation methods that prolong their shelf life and maintain the high levels of bioactive compounds are necessary (Morais et al, 2017;Araújo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%